The Role of APEC in Peruvian Foreign Economic Policy Consolidation - Castro Silva, Julissa (2017)
The present article focuses on the role of APEC in the consolidation of Peruvian Foreign Economic policy. It analyzes if this Forum has represented some type of influence and in what way it has become evident. This study shows that APEC, with the leadership of the United States, has exerted a relevant external influence, first, channeling the liberalization principles of the World Trade Organization (WTO), and then, through the deepening of its own agenda that institutionalized a bilateral and multilateral opening strategy after the Asian crisis.